Improving farm profitability also reduces the carbon footprint of milk production in intensive dairy production systems. (20th August 2019) - Jayasundara, Susantha; Worden, David; Weersink, Alfons; Wright, Tom; VanderZaag, Andrew; Gordon, Robert; Wagner-Riddle, Claudia
Abstract: Standard life cycle assessment and economic analysis methods were used to determine the carbon footprint (CF) of milk production and financial performance of a representative sample of dairy farms in Ontario, Canada to assess if there is a trade-off between these two different sustainability measures. Across the 142 dairy farms, CF of milk varied by about 4-fold, from 0.441 to 1.732 CO2 eq kg −1 FPCM, a much larger variation than estimated using spatially disaggregated statistical data. Emissions from enteric fermentation and those resulting from the production and supply of feed were the largest contributors to the CF of milk (44% and 36%, respectively). Dairy profits per cow averaged CA4848 per year but ranged from CA2530 to 7151 across sample farms. These financial returns were inversely correlated with the CF of milk production, suggesting that rather than a trade-off between GHG emissions intensity and economic performance, there is instead a synergy of the two sustainability indicators. Using a linear regression approach we find that a reduction in the CF of milk production can be achieved while simultaneously improving the profitability of dairy farms. This synergy was largely determined by farm characteristics related to livestock productivity (e.g. milk production per cow) and feeding practices (e.g. herd level total feed use and reliance on purchased feed). Our results suggest that in the absence of explicit GHG reduction policies targeting dairy farms, the main incentive for reducing farm-level GHG emissions could result from the economic pressure on farmers to increase their profitability per cow or per ha. Highlights: There was a 4-fold difference in the carbon footprint per unit of milk production across the farms. There is no trade-off between GHG emissions intensity and economic performance. Enhancing the production efficiency results in an improvement across both sustainability measures. This synergy was largely determined by farm characteristics related to livestock and feeding practices.